2015
DOI: 10.1017/s0007114514003808
|View full text |Cite
|
Sign up to set email alerts
|

The validation of a computer-based food record for older adults: the Novel Assessment of Nutrition and Ageing (NANA) method

Abstract: Dietary assessment in older adults can be challenging. The Novel Assessment of Nutrition and Ageing (NANA) method is a touch-screen computer-based food record that enables older adults to record their dietary intakes. The objective of the present study was to assess the relative validity of the NANA method for dietary assessment in older adults. For this purpose, three studies were conducted in which a total of ninety-four older adults (aged 65 -89 years) used the NANA method of dietary assessment. On a separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(58 citation statements)
references
References 35 publications
(40 reference statements)
5
52
0
1
Order By: Relevance
“…This indicates that the tablet app is suitable for accurately estimating intakes at an individual level. Our finding of narrow LOA is consistent with the results by Timon et al [26] but in contrast to studies comparing either a smartphone app or a Personal Digital Assistant (PDA) with 24-h recall [15,19,29]. As suggested by the authors of these latter studies, this could be possibly due to measurement errors found in the reference measure (24-h recall), which itself is not a measure of absolute intakes as it is not representative of habitual intakes and is prone to recall bias and misreporting [19], whereas we were able to measure absolute food intake with our use of the current gold standard (measured food intake/food waste method).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This indicates that the tablet app is suitable for accurately estimating intakes at an individual level. Our finding of narrow LOA is consistent with the results by Timon et al [26] but in contrast to studies comparing either a smartphone app or a Personal Digital Assistant (PDA) with 24-h recall [15,19,29]. As suggested by the authors of these latter studies, this could be possibly due to measurement errors found in the reference measure (24-h recall), which itself is not a measure of absolute intakes as it is not representative of habitual intakes and is prone to recall bias and misreporting [19], whereas we were able to measure absolute food intake with our use of the current gold standard (measured food intake/food waste method).…”
Section: Discussionsupporting
confidence: 94%
“…These correlations compared favourably with results from other validation studies of technology-assisted dietary assessment methodologies [13,15,19,26,27]. Carter et al [19] compared a smartphone app with 24-h recalls and found correlations ranging from 0.63 to 0.83, which are quite a bit lower than those seen in our study.…”
Section: Discussionsupporting
confidence: 76%
“…This study also suggests that nutritionists may provide more accurate estimates of portion size with less variance in the estimates by nutritionists compared to younger and older adults. In terms of the development of the NANA system, it was concluded that higher accuracy would be achieved by a nutritionist making portion size assessment from a photograph of a meal and this was incorporated into the design of the system (17,18). These results support the recent developments in dietary assessment and technology which have shown that taking the onus of portion size estimation off the individual and putting it on a trained researcher yields accurate results compared to weighed methods of dietary assessment (13,14).…”
Section: Resultsmentioning
confidence: 73%
“…The results of this project were used to inform the development of the dietary component of a computer based assessment tool for older adults, i.e. the "NANA" (Novel Assessment of Nutrition and Ageing) system (17,18). In terms of the portion size assessment component of the NANA system, two possible strategies for assessing portion size were considered.…”
Section: A Comparison Of Food Portion Size Estimation By Older Adultsmentioning
confidence: 99%
“…Whereas previous studies have compared user with professional entry of the same record [9], or user with professional entry of records taken on separate occasions [17], this study eliminated the biases associated with user entry, (e.g. selection of appropriate food item, estimation of portion size [13]).…”
Section: Strengths and Limitationsmentioning
confidence: 99%